Conflict Dynamics in Organizational Decision-Making. Muslim Accommodation in Swimming Pools - Michalowski Ines; Oliver Schmidt Max (Journal of Organizational Sociology)
This study examines how organizational decisions affect conflicts over Muslim accommodation (burkini permissions and separate women’s hours) in German swimming pools. We compare pools in similar demographic areas, representing four models of Muslim accommodation. We find that conflict dynamics and organizational management strategies differ across the cases: (1) The multicultural pool (burkini allowed, separate women’s hours offered) faces disputes over special rights claims by different groups and concerns about segregation. The organizational response involves façade-building and the allocation of additional resources. (2) The universalist pool (burkini allowed, no separate hours) has the lowest level of conflict, downplays cultural differences, and ensures that the same rules apply to all users. (3) The assimilationist pool (no burkini, no separate women’s hours) experiences conflicts over sharing limited resources with those perceived as different and adopts a laissez-faire response where the majority prevails. (4) The segregationist pool (no burkini but separate women’s hours) experiences open conflict between the majority and minority, with organizational responses focused on disciplining and controlling Muslim users.